THE APPLICATION OF HUMAN RESOURCE MANAGEMENT TO THE FINANCIAL MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDES) BY UTILIZING DIGITAL TECHNOLOGY - Rahayu, Estri Purwani; Adi, Handaru Indrian Sasmito (Airlangga Development Journal, 2024)
Digital financial reporting provides convenience for BUMDes business managers in accessing well-structured data information. In recent years, financial management has evolved from its initial definition, which only focuses on fund collection and asset management, especially in analysing the sources of funds and how they are used to achieve maximum profit for the company. This research uses a qualitative method with a literature approach. Data came from references to the Village Government Law, relevant research journals, and books on village financial management. The data was analysed using the document analysis method. The results of this study state that BUMDes managers must have internalisation skills in managing records. They should be actively involved in drafting financial standard operating procedures (SOPs) and be able to compile financial reports and administrative records digitally. This will make the managers accountable for using capital funds provided by the government. Keywords: Financial Management, BUMDes, Digital Technology, Human Resource Management